1979
DOI: 10.1177/016402757911006
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Self-Related Health among the Aged

Abstract: Self-rated health among a sample of older persons is investigated via a simple path analysis model. The strongest predictor of self-rated health is a health index measuring reported conditions and confinement at home in bed. Income and education have small but significant direct effects on self-rated health suggesting that elderly of lower SES tend to evaluate their health as poorer than those of higher SES who are of similar health status (measured by the health index). Age, ethnicity, and sex affect self-rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Self report measures have demonstrated good reliability, validity, and agreement with physician's diagnoses [42]. Nonetheless health assessments were dependent on the participants' ability to accurately recall medical diagnoses and also on their seeking health care.…”
Section: Discussionmentioning
confidence: 99%
“…Self report measures have demonstrated good reliability, validity, and agreement with physician's diagnoses [42]. Nonetheless health assessments were dependent on the participants' ability to accurately recall medical diagnoses and also on their seeking health care.…”
Section: Discussionmentioning
confidence: 99%
“…Further, as the APOE 4 allele may increase the risk of some health problems associated with CD, the relationship between APOE genotype and CD may be explained in part by unreported physical health problems. However, it is important to note that studies have found that objective measures are the strongest predictors of singleitem self-report measures of health among the elderly [40] and that such single-item self-report measures have good reliability [41] and validity [42] in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Responses were coded 0 (absent) or 1 (present) and items were summed to obtain a cumulative health problem variable. Single‐item self‐report measures of health are associated with objective measures of health 46…”
Section: Methodsmentioning
confidence: 99%